Prevalence rate of PTSD, depression and anxiety symptoms among Saudi firefighters - Alghamdi, Mohammed; Hunt, Nigel; Thomas, Shirley (SciTechnol, 2016)
Background: Firefighters have a high likelihood of being exposed to a variety of traumatic events. Traumatic events may occur during any rescue, such as providing aid to seriously injured victims or seeing a colleague injured. The psychological cost of this exposure may increase the risk of long-term problems such as PTSD symptoms, anxiety and depression. Moreover, firefighters who are injured in the line of duty sometimes have to retire as a consequence of their injury.